2004
DOI: 10.1016/j.jpainsymman.2003.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Pain characteristics and treatment outcome for advanced cancer patients during the first week of specialized palliative care

Abstract: To examine pain in cancer patients referred for specialized palliative care, we described pain characteristics and medication on admission, examined changes in pain during the first week, and searched for predictors of initial pain intensity and treatment outcome. On arrival in the department (T0) and after one week (T1), pain was evaluated with the Edmonton Symptom Assessment System (ESAS) and EORTC QLQ-C30. Analgesics were recorded. We investigated the associations between initial pain scores as well as diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 34 publications
2
65
0
4
Order By: Relevance
“…These results are similar, in part, to other findings where researchers have found, for example, bone metastases, BTP, and the presence of metastases, associated with higher pain intensity. 13,14,16 …”
Section: Discussionmentioning
confidence: 99%
“…These results are similar, in part, to other findings where researchers have found, for example, bone metastases, BTP, and the presence of metastases, associated with higher pain intensity. 13,14,16 …”
Section: Discussionmentioning
confidence: 99%
“…For 314 patients admitted to a palliative care ward in Italy over 1 week, pain decreased from an average of 7 to 4 (p < 0.001), as did many other symptoms measured by the Edmonton Symptom Assessment Scale (ESAS) [90]. In another study of 267 cancer patients admitted with pain to a palliative care ward in Denmark and assessed with the ESAS and the European Organization for Research Treatment Cancer Quality of Life Questionnaire, significant decreases were found in pain measures and for other symptoms after 1 week [91]. Pain improvement has also been reported in other settings.…”
Section: Clinical Trialsmentioning
confidence: 97%
“…Factors associated with high pain intensity were neuropathic pain, mixed neuropathic/nociceptive pain etiologies and bone metastases. The authors concluded that there was need for improvement in patients with these categories of pain, both through research and recording of treatment outcomes (20).…”
Section: Cancer-related Neuropathymentioning
confidence: 99%